Adoption of Free and Open-Source Software in the Angolan Public Sector - Silva, Domingos G.; Coutinho, C.; Costa, C. (2024)
The growing demand for innovative services has put pressure on governments to adapt quickly. Digital transformation, while an appropriate response, faces significant challenges, particularly in developing countries, such as high costs and dependence on technology providers. Several studies have suggested the adoption of Free and Open-Source Software (FOSS) as a strategy to promote digital transformation. FOSS has several benefits, which include, but are not limited to, its cost-effectiveness, flexibility, and security. The main objective of this research is to investigate the adoption of FOSS in the public sector, with an emphasis on health in developing countries, such as Angola. This thesis is motivated by the belief that the search for FOSS is not only a low-cost alternative to proprietary solutions, but a way to promote technological independence and flexibility to customize systems according to specific needs. Following a mixed methodological approach, from "Natural Sciences" and "Design Science", the research offers a comprehensive overview of the FOSS literature and identifies the key factors influencing the acceptance/adoption of FOSS. In addition, it provides a detailed analysis on the crucial role of FOSS in overcoming interoperability challenges. It obtained as results bibliometric clusters, a theoretical model of FOSS adoption, and an architecture to improve the accessibility of health care in remote areas. These results suggest to decision-makers, especially in developing countries, that FOSS promotes self-sufficiency and digital inclusion, and plays a key role in the digital transition.